2013
DOI: 10.18814/epiiugs/2013/v36i1/007
|View full text |Cite
|
Sign up to set email alerts
|

2883 Ma commencement of BIF deposition at the northern edge of Congo craton, southern Cameroon: New zircon SHRIMP data constraint from metavolcanics

Abstract: The deposition of BIF is linked to a contemporaneous process in which clastic sediments from the continent were being deposited in the ocean along with the upwelling of hydrothermal fluids at the Mid-Ocean-Ridge (MOR) (Bau and Möller, 1993; Clout and Simonson, 2005 and Beukes and Gutzmer, 2008). Lavas intercalated with BIF provide a direct tool for constraining the timing of BIF formation in a paleobasin. The determination of BIF depositional age is vital to date key events in the evolution of the biosphere. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 34 publications
3
19
0
Order By: Relevance
“…The Ntem Complex is part of the Congo craton and represents the oldest lithologic group in Cameroon. This complex hosts several iron deposits at various stages of resource definition and development (see [23][24][25]39] and www.sundanceresources.com.au, www.afferro-mining.com).…”
Section: Geological Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…The Ntem Complex is part of the Congo craton and represents the oldest lithologic group in Cameroon. This complex hosts several iron deposits at various stages of resource definition and development (see [23][24][25]39] and www.sundanceresources.com.au, www.afferro-mining.com).…”
Section: Geological Reviewmentioning
confidence: 99%
“…In this paper we characterize metasediments associated with BIF in the Ntem complex and date detrital zircons from them in order to unravel their provenance and the palaeodepositional environment. The mineralogy, age and the structural setting of the BIF have been reported [23][24][25]39].…”
Section: Geological Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Camiron Ltd., Caminex Ltd., Camina Ltd., Aucam Ltd., G‐stones Resources Ltd.; Divine Mining Ltd., and Geocam Mining Ltd.) have carried out field surveys and preliminary geochemical tests. The exploration results have revealed that the high magnetic anomalies are related to magnetite‐rich BIFs, such as in the Mbalam (Suh et al, ; Chombong & Suh, ), Nkout (Suh et al, ) and Bikoula (Teutsong et al, ) areas. Moreover, new iron‐rich bodies, namely, Elom (Ganno et al, ), Grand Zambi (Ganno et al, ), and Kouambo (Ganno et al, ), have been discovered in the Ntem Complex.…”
Section: Introductionmentioning
confidence: 99%